Entrepreneurship Training and Self-Efficacy on Entrepreneurship Interest in Midwifery Practice - Dina Dewi Anggraini; Marlynda Happy Nurmalita Sari (Poltekkes Kemenkes Medan, 2023)
This study aims to determine the effect of entrepreneurship training and self-efficacy training on entrepreneurship interest in midwifery practice in final year DIII Midwifery Study Program Blora Poltekkes Kemenkes Semarang. The sampling technique used a total sampling technique of 52 students. Methods of data collection using a questionnaire. Data analysis techniques using multiples regression. The results showed that there was an influence of entrepreneurship training (X1) and self-efficacy (X2) on entrepreneurship interest in midwifery practice (Y). Multiple regression analysis with a Significance value (Sig.) of 0.000, which means that there is a significant influence between entrepreneurship training and self-efficacy on entrepreneurship interest in midwifery practice in Final Level Students of Diploma III Midwifery Study Program Blora Poltekkes Kemenkes Semarang. Keywords: entrepreneurship training; self-efficacy; entrepreneurship interest